Estratégias de hedge dinâmico: um estudo comparativo - Heilbrun, Daniel Montero (2017)
Several theoretical works have been developed in the last five decades proposing texting delta-hedge strategies when the premises of the Black e Scholes (1973) are relaxed. This paper sets out to find the best delta-hedge strategy in the presence of transaction costs with the price series that follows a GARCH (1,1) process. This paper analyzes and compare four different delta-hedge strategies: Black e Scholes (1973), modified volatility (Leland (1985)), Asset Tolerance Strategy (Henrotte (1993)) e Variable Banwidth Around Delta (Whalley e Wilmott (1997)).